Insurers’ Responsibility in Insurance Liability - ANTONOVA, Natalia A.; LUNYOVA, Elena N. (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
Study of insurance as a legal tool of redistribution of property risks in various public relations is especially topical in the situation of unstable economic environment and progressing change of legal basis. Consumers of insurance services name distrust to insurance organizations as one of the reasons for refusal from insurance. Despite the existing diversity of works on insurance, there is still no single opinion on understanding the differences in notions of insurers’ performing liabilities on the agreement and responsibility of insurance organizations. This article analyzes legal regulation of rights and liabilities of insurers in insurance liability for the purpose of determining the reasons for refusal from paying insurance indemnity and determining the limits in the notions of insurer’s performing his responsibility in insurance liability.